Impact of antidumping measures on international trade: Growing South–South tensions?. Issue 3 (2nd April 2020) - Kang, Jong Woo; Ramizo, Dorothea
ABSTRACT: In the last two decades, developing economies have become prominent users of antidumping measures in their trade protection policies. However, few empirical studies have studied the impact of antidumping measures according to region, development status, and product groups. This paper addresses this gap by investigating empirically the trade impact of antidumping measures on trade between different region and country groupings. Using various econometric models, this paper estimates the trade impact of such measures on exports to different country groups from North America, the European Union, and developing Asia from 2000–2015. Developing countries have become more frequent initiators of antidumping measures than before, in particular against imports from other developing countries. Robust empirical evidence suggests that antidumping measures by countries outside the Organisation for Economic Cooperation and Development and non-developing Asia have particularly adverse effects on developing Asian economies.